Bioleaching Of Gold Pyrite Tailings With Adapted Bacteria - Y. A. Attia (Society for Mining, Metallurgy & Exploration, 1987)
Auriferous sulfide ores often contain very finely disseminated gold and other precious metal particles inside the sulfide crystals. The encapsulation of precious metal particles gives rise to the refractory nature of such ores to current extraction methods. As a result, these fractions are frequently lost in the tailings. The purpose of this work was to investigate the feasibility of pretreating these refractory tailings with bioleaching before employing standard extraction techniques such as cyanidation. Leadville gold ore tailings containing auriferous pyrite were first concentrated by froth flotation. The pyrite concentrate was treated for different periods of time with 12 weeks adapted thiobacillus ferrooxidans before cyanide leaching. The bioleaching of the concentrate before cyanide leaching increased the gold extraction from 32% to 95% and that of silver from 48% to more than 98%.